2005
DOI: 10.2337/diacare.28.3.514
|View full text |Cite
|
Sign up to set email alerts
|

Sex Disparities in Treatment of Cardiac Risk Factors in Patients With Type 2 Diabetes

Abstract: OBJECTIVE -Diabetes eliminates the protective effect of female sex on the risk of coronary heart disease (CHD). We assessed sex differences in the treatment of CHD risk factors among patients with diabetes. CONCLUSIONS -Women with diabetes received less treatment for many modifiable CHD risk factors than diabetic men. More aggressive treatment of CHD risk factors in this population offers a specific target for improvement in diabetes care. RESEARCH DESIGN AND METHODS Diabetes Care 28:514 -520, 2005D iabetes co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

36
230
4
12

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 316 publications
(282 citation statements)
references
References 39 publications
36
230
4
12
Order By: Relevance
“…[6] Results of our study shows that the level of LDL, TC & TG were significantly higher in Type 2 diabetics, which is in accordance with the study conducted by Wexler et al [7] Diabetic patients with elevated HbA1c and altered Lipid profile can be considered as a very high risk group for severe complications. Improving glycemic control can substantially reduce the risk in diabetic patients.…”
Section: Discussionsupporting
confidence: 91%
“…[6] Results of our study shows that the level of LDL, TC & TG were significantly higher in Type 2 diabetics, which is in accordance with the study conducted by Wexler et al [7] Diabetic patients with elevated HbA1c and altered Lipid profile can be considered as a very high risk group for severe complications. Improving glycemic control can substantially reduce the risk in diabetic patients.…”
Section: Discussionsupporting
confidence: 91%
“…Our observations are consistent with other population-based (Kerr et al, 2004;Saydah et al, 2004) and clinicbased studies Kennedy et al, 2005;Wexler et al, 2005) of the general population with Type 2 diabetes. Second, we found that similar and substantial numbers of diabetes patients with and without SMI in this study met criteria for the metabolic syndrome, a cluster of risk factors including elevated cholesterol and blood pressure along with obesity and hyperglycemia that has been associated with increased mortality overall and from CVD in men and heightened risk of CVD in women .…”
Section: Discussionsupporting
confidence: 82%
“…Also, more men than women (20-39 years) were taking antihypertensive medication. This is in line with a study reporting that fewer women than men were treated for modifiable risk factors of T2DM (31). Nevertheless, in our cohort, more women than men aged O40 years were taking antihypertensive medication.…”
Section: Discussionsupporting
confidence: 69%